Media Relations as Public Relations Consistency in Building Company and Organizational Reputations - Putri, Tri Della; Lestari, Yayuk (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
Media relations is a form of communication strategy for a Public Relations professional in maintaining relations with the media. Establishing and maintaining good relations with the media is very important for a Public Relations. Because the media is a means of publication, where all information about the company is channeled besides that the media is also a means to build reputation. The research method used is library research.